A general concept for highly efficient covalent laser patterning of graphene based on silver carboxylates - Wei, Tao; Liu, Xin; Al-Fogra, Sabrin; Bachmann, Julien; Hauke, Frank; Hirsch, Andreas (Chemical Communications, 2021)
Three novel types of spatially resolved graphene architectures GA, GB, and GC respectively bearing CH3-, C6H5- and C3F7 groups are efficiently constructed by newly developed laser-writing concepts using silver carboxylates as corresponding photosensitizers. These 2D-structured samples are unequivocally characterized by Raman spectroscopy and SEM-EDS. This journal is
CRIS-Team Scopus Importer:2021-05-21